Penerapan Strategi Kontekstual Media Papan Bilangan dalam Pembelajaran Matematika Siswa Kelas 1 Sekolah Dasar - Rangkuti, Hamidah Farhani; Wandini, Rora Rizky; Zachri Wahyudi, Zulfa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Contextual strategies are suitable approaches for lower grade students. The purpose of this study was carried out to facilitate students in learning mathematics using contextual learning. The method used in this study is qualitative with a library research study approach, data collection techniques in this study include observation, and documentation. While the data analysis used is descriptive analysis. From the results of data analysis, it shows that contextual strategies and pajum media have a very close relationship in mathematics learning, especially for grade 1 elementary school children. Contextual strategies themselves must have real experience in implementing them. Therefore, when implementing it in grade 1 elementary school in mathematics learning, there must be a learning medium. Because at the age of 1st grade elementary school, it leads to Jean Piaget's theory in the concrete operational stage. Which is where this stage is a major turning point.